RELIABILITY AND CONSTRUCT VALIDITY OF THE SELF ADJUSTMENT SCALE - Andika Agus Setiawan; Resti Handayani; Aulia Woro Hapsari; Dini Fajar Khairunisa (P3I UMSurabaya, 2024)
The purpose of this study is to examine the reliability and construct validity of self-adjustment, to find dimensions and indicators that can form self-adjustment. self-adjustment measured by the dimensions of recognition, participation, conformity, altruism, and social approval. The population in this study were new students of the psychology study program at Muhammadiyah Purwokerto University in the 2024/2025 academic year, totaling 302 new students. The sample of this study was 172 new students. The sampling technique in this study used a random sampling. Data collection methods use a self-adjustment scale. Research data were analyzed with Structural Equation Modeling (SEM) through the Smart PLS 3.2.8 program. Based on the analysis results, the dimensions and indicators that form the construct of self-adjustment are declared valid and reliable. The most dimension that reflects the construction of self adjustment is a recognition with a loading factor value is 0,947. The lowest dimension that reflects the construct of self adjustment is social approval, with a loading factor 0,476. This research shows that all dimensions and indicators are able to reflect and form the construct of self-adjustment. Thus, the measurement model can be accepted because the theory was described self-adjustment is consistent with empirical data obtained from the subject.